Structure and magnetism of a binuclear CuII pyrophosphate: transition to a 3D magnetic behaviour studied by single crystal EPR - Sartoris, Rosana Patricia (2015)
A binuclear CuII compound [Cu2(bpa)2(P2O7)(H2O)2]·2.5H2O, 1, (bpa = 2,2-bipyridylamine), with pairs of CuII ions bridged by one pyrophosphate tetra-anion, was synthesized and crystallized. Its triclinic structure was determined by single-crystal X-ray diffraction. Electron paramagnetic resonance (EPR) spectra of single crystal samples of 1 were recorded for a fixed orientation of the magnetic field (B0) as a function oftemperature (T) between 4.7 and 293 K, and at T = 4.7, 50 and 293 K, as a function of the orientation of B0. Below ∼8 K, the spectra are assigned to two types of mononuclear crystal defects hyperfine-coupled to one copper and two nitrogen nuclei. The g-matrices and hyperfine couplings at these T provide information about the structures of these defects. Above 10 K, the spectrum is dominated by the response of the bulk binuclear CuII material, showing hyperfine interactions with two copper nuclei, collapsing to asingle peak above 18 K when the units are magnetically connected, and the magnetic behaviour becomes 3D. We attribute the results above 10 K to the interplay of an AFM intrabinuclear exchange interaction J0 = −28(3) cm−1 (defined as Hex = −J0S1·S2), and three orders of magnitude weaker exchange coupling with average magnitude |J1| ≥ 0.022 cm−1 between CuII ions in neighbouring binuclear units. The interplays between structure, exchange couplings, magnetic dimension and spin dynamics in the binuclear compoundare discussed. A previously unreported situation, where the structure of the spectra arising from the anisotropic spin?spin interaction term (D) within the binuclear unit is averaged out, but the forbidden half field transition is not, is observed and explained.